Evaluation of the School's Annual Work Plan (RKT) Program in Improving the Quality of Education at SDN 49 Bengkulu City - Meylindo, Deli; Viani, Okta (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstrac: This study aims to evaluate the implementation of the school programs outlined in the Annual Work Plan at SDN 49 Bengkulu City and to examine their contribution to improving the quality of education. The evaluation was conducted using a descriptive qualitative approach through observations, interviews, and documentation. First, the context of the Annual Work Plan program includes the strategic plan and program objectives. Second, the inputs of the Annual Work Plan program—such as teachers participating in training and workshops—have an impact on improving the quality of education. Students who receive character reinforcement are able to demonstrate discipline, responsibility, and social awareness. Third, the implementation process of the annual plan program is generally quite good, but not yet optimal, as evidenced by the school’s accreditation declining from A to B due to missing important documents and the lack of understanding among administrative staff and teachers regarding the archiving system. Fourth, the products of the Annual Work Plan program have utilized the results of the School Self-Evaluation (EDS) and quality report as the basis for program development, reflecting an evidence-based approach. However, disparities in implementation among teachers, limitations in differentiated instruction, and weaknesses in monitoring and evaluation systems have contributed to the decline in accreditation quality. Thus, it can be concluded that the evaluation of the Annual Work Plan is able to illustrate the aspects of educational quality that need improvement. Therefore, it is recommended that to improve the quality of education, schools should enhance the evaluation of their annual work plan program.Keywords: Evaluation, School Annual Work Plan Program, Quality of Education. Abstrak: Penelitian ini bertujuan untuk mengevaluasi pelaksanaan program sekolah yang tertuang dalam Rencana Kerja Tahunan di SDN 49 Kota Bengkulu serta mengkaji kontribusinya terhadap peningkatan mutu pendidikan. Evaluasi dilakukan dengan pendekatan kualitatif deskriptif melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Pertama, Konteks program Rencana Kerja Tahunan meliputi rencana strategis, dan tujuan program. Kedua, Input program Rencana Kerja Tahunan seperti guru mengikuti diklat dan workshop berdampak pada peningkatan mutu pendidikan, Siswa yang diberikan penguatan karakter mampu bersikap disiplin, tanggung jawab, dan kepedulian sosial. Ketiga, Proses pelaksanaan program rencana tahunan secara umum sudah cukup bagus, namun belum optimal, terlihat akreditasi sekolah mengalami penurunan, dari A turun menjadi B, disebabkan dokumen-dokumen penting tidak ditemukan, tenaga adminstrasi dan para guru tidak paham tentang sistem ke arsipan. Keempat, produk program Rencana Kerja Tahunan telah memanfaatkan hasil Evaluasi Diri Sekolah (EDS) dan raport mutu sebagai dasar penyusunan program, yang mencerminkan pendekatan evidence-based. Namun, terjadi disparitas pelaksanaan antar guru, keterbatasan dalam diferensiasi pembelajaran, serta lemahnya sistem monitoring dan evaluasi, sehingga mutu akreditasi menurun. Dengan demikian, dapat disimpulkan bahwa evaluasi Rencana Kerja Tahunan mampu menggambarkan mutu pendidikan yang perlu diperbaiki. Sehingga dapat disarankan, untuk meningkatkan mutu pendidikan, maka tingkatkanlah evaluasi program rencana kerja tahunan di sekolah.Kata kunci: Evaluasi, Program Rencana Kerja Tahunan (RKT) Sekolah, Mutu Pendidikan.